ANALISIS MENGENAI DAMPAK LINGKUNGAN (AMDAL) PADA PEDAGANG IKAN DI PASAR SENTRAL - Marina Marina; Rista Aulia Arbay; Monica Desiani Luju (Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the potential environmental impact caused by fish trading activities at Mimika Central Market, particularly in the activities of fish reception, storage using ice blocks, cutting, and cleaning. These activities have the potential to produce organic solid waste and liquid waste containing blood, mucus, and fat, which can cause a decline in environmental quality. The method used in this study is an Environmental Impact Assessment (EIA), which includes the stages of identification, prediction, and evaluation of environmental impacts, as well as the preparation of an Environmental Management Plan (EMP) and an Environmental Monitoring Plan (EMP). The analysis results show that the main environmental impacts identified include unpleasant odors, increased BOD and COD content in wastewater, clogged drainage channels, and potential health hazards and disease vectors. Recommended environmental management efforts include waste sorting at the source, installation of filters and grease traps, drainage system improvements, regular waste transportation, implementation of cleanliness operational standards, and periodic environmental quality monitoring. Overall, the implementation of RKL and RPL is expected to minimize the negative impacts of fish trading activities and support the creation of a clean, healthy, and sustainable market environment.